The Analysis of Content of Bachelor Study Programme of Music Teacher Training in Lithuania: Attitude of Foreign and Lithuanian Students - Rauduvaitė, Asta; Wang, Linlin (Pedagogika, 2018)
Teacher training institutions play a significant role in preparing future music teachers. Lithuanian University of Educational Sciences (now Vytautas Magnus University, Academy of Education) as an institution that educates professional teachers and implements the study programmes of music teacher education. The aim of the research is to reveal the results of the analysis of the content of music teacher education programme highlighting the attitude of foreign and Lithuanian students. The research shows that most study subjects are thought to be very important by future music teachers, especially music knowledge and pedagogical studies. During the Bachelor studies, the majority of students (Chinese and Lithuanian) have gained the abilities at the professional level.